AID and APOBECs span the gap between innate and adaptive immunity - Moris, Arnaud; Murray, Shannon; Cardinaud, Sylvain (Frontiers in Microbiology, 2014)
The AID/APOBEC cytidine deaminases participate in a diversity of biological processes from the regulation of protein expression to embryonic development and host defenses. In its classical role, AID mutates germline-encoded sequences of B cell receptors, a key aspect of adaptive immunity, and APOBEC1, mutates apoprotein B pre-mRNA, yielding two isoforms important for cellular function and plasma lipid metabolism. Investigations over the last ten years have uncovered a role of the APOBEC superfamily in intrinsic immunity against viruses and innate immunity against viral infection by deamination and mutation of viral genomes. Further, discovery in the area of HIV infection revealed that the HIV viral infectivity factor (Vif) protein interacted with APOBEC3G, targeting it for proteosomal degradation, overriding its antiviral function. More recently, our and others’ work have uncovered that the AID and APOBEC cytidine deaminase family members have an even more direct link between activity against viral infection and induction and shaping of adaptive immunity than previous thought, including that of antigen processing for cytotoxic T lymphocyte (CTL) activity and natural killer (NK) cell activation. Newly ascribed functions of these cytodine deaminases will be discussed, including their newly identified roles in adaptive immunity, epigenetic regulation, and cell differentiation. Herein this review we discuss AID and APOBEC cytodine deaminases as a link between innate and adaptive immunity uncovered by recent studies.